Judicial Accoutability: International Standards and Experiences from Some Countries - Trinh, Quoc Toan (H. : ĐHQGHN, 2019)
Judicial accountability is a matter of great concern in the international, regional and national community as judicial accountability assures accountability for serious judicial misconduct, such as crimes, corruption and human rights violations. However, judicial accountability is understood and implemented through a variety of mechanisms and forms in different countries. One of the contentious and controversial issues is how to put judicial accountability in relation to another core principle of the judiciairy - judicial independence. That is why, the international and some regional communities have made efforts to develop a number of standards and recommendations on the mechanisms and forms of judicial accountability